Piezo1 Knockout Improves Post-Stroke Cognitive Dysfunction by Inhibiting the Interleukin-6 (IL-6)/Glutathione Peroxidase 4 (GPX4) Pathway - Tang L; Xie D; Wang S; Gao C; Pan S (Dove Medical Press, 2024)
Lujia Tang,* Di Xie,* Shangyuan Wang, Chengjin Gao, Shuming Pan Department of Emergency, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200092, People's Republic of China*These authors contributed equally to this workCorrespondence: Shuming Pan; Chengjin Gao, Email panshuming@xinhuamed.com.cn; gaochengjin@xinhuamed.com.cnBackground: Cerebral infarction often results in post-stroke cognitive impairment, which impairs the quality of life and causes long-term disability. Astrocytes, the most abundant glial cells in the central nervous system, have a crucial role in cerebral ischemia and neuroinflammation. We explored the possible advantages of interleukin-6 (IL-6), a powerful pro-inflammatory cytokine produced by astrocytes, for post-stroke cognitive function.Methods: Mendelian randomization was applied to analyze the GWAS database of stroke patients, obtaining a causal relationship between IL-6 and stroke. Further validation of this relationship and its mechanisms was conducted. Using a mouse model of cerebral infarction, we demonstrated a significant increase in IL-6 expression in astrocytes surrounding the ischemic lesion. This protective effect of Piezo1 knockout was attributed to the downregulation of matrix metalloproteinases and upregulation of tight junction proteins, such as occludin and zonula occludens-1 (ZO-1).Results: Two-step Mendelian randomization revealed that IL-6 exposure is a risk factor for stroke. Moreover, we conducted behavioral assessments and observed that Piezo1 knockout mice that received intranasal administration of astrocyte-derived IL-6 showed notable improvement in cognitive function compared to control mice. This enhancement was associated with reduced neuronal cell death and suppressed astrocyte activation, preserving ZO-1.Conclusion: Our study shows that astrocyte-derived IL-6 causes cognitive decline after stroke by protecting the blood-brain barrier. This suggests that piezo1 knockout may reduce cognitive impairment after brain ischemia. Further research on the mechanisms and IL-6 delivery methods may lead to new therapies for post-stroke cognition.Keywords: cerebral infarction, neuroinflammation, astrocytes, blood-brain barrier, tight junctions